Description of Nilssondytes diversus gen. et sp. nov. from Venezuela (Coleoptera, Adephaga, Dytiscidae, Cybistrinae) - Miller, Kelly B. (2024)
A new genus, Nilssondytes gen. nov., is described for a unique new species, Nilssondytes diversus sp. nov., from Venezuela. This paper corrects an inadvertent mistake in a paper by the authors (Miller et al. 2024) in which the collection of deposition of the holotype of the species was not indicated making the new species unavailable which, therefore, made the new genus unavailable. A review of the relevant parts of the International Code of Zoological Nomenclature is included. Diagnostic features of the new genus and species are discussed and illustrated.